Operation optimization on the large-scale CHP station composed of multiple CHP units and a thermocline heat storage tank - Lai, Fen; Wang, Shan; Liu, Ming; Yan, Junjie (Energy conversion and management, 2020)
[Display omitted] •Heat storage is applied to realize heat-power decoupling for large scale CHP station.•Optimization models considering CHP unit detail energy consumption were developed.•Operation of thermocline storage tank and CHP units can be scheduled globally.•~133 kUSD per heating period can be saved for the reference case analyzed. Combined heat and power (CHP) is used around the world to enhance energy efficiency. The power load and heating loads are coupled in CHP units. Therefore, heat-power decoupling is essential for CHP units because it serves as the balancing power units to accommodate intermittent renewable power. Heat storage is an effective way to enhance CHP station flexibility. Considering the detail energy consumption characteristics of CHP units, this study investigated how to operate the CHP station, which is composed of multiple parallel CHP units and a thermocline heat storage tank, under constrained heating and power loads. Operation optimization models were developed, and particle swarm optimization was applied. Then, a case study was carried out. The minimum adjustable power load of the CHP unit is decreased by 12% through integrating heat storage when the heating load is 300 MW. The operation of the thermocline storage tank and CHP units could be scheduled globally with the developed optimization models. The total coal consumption could be decreased by 10.27 tons for the analyzed typical day, and the average standard coal consumption rate for power generation reduces by 1.16 g·kW−1h−1. Additional ~133 kUSD per heating period can be saved.